A transitional wear-resistant and corrosion-resistant coating for electric power connection fittings and a preparation method thereof
By applying a composite transition wear-resistant and corrosion-resistant coating on the connecting metal, the problem of easy wear and corrosion-resistant metal in overhead transmission lines is solved, and the galvanized layer is easily damaged in strong wind and sand areas is achieved, which achieves good wear and corrosion resistance, ensures the safe and stable operation of the line and reduces operation and maintenance costs.
Patent Information
- Application Number
- CN202010752348.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-07-30
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2040-07-30
AI Technical Summary
The connecting metal tools in the active overhead transmission lines are prone to severe wear and tear in strong winds and sand areas, resulting in a decrease in effective load-bearing area and causing power outages. At the same time, the existing hot-dip galvanizing anti-corrosion treatment has problems with water pollution and soil pollution, and the galvanized layer is easy to be damaged, which cannot effectively ensure the corrosion resistance of the metal tools.
A composite transition wear-resistant and corrosion-resistant coating is used. The coating is composed of a bottom layer and a top layer. The bottom layer contains 6.80% to 7.50%, chromium 14.60% to 15.40%, silicon carbide 20.00% and balanced iron. The top layer contains 5.30% to 5.90%, chromium 11.10% to 11.80%, silicon carbide 40.00% and balanced iron. The target material is prepared by induction smelting method and powder metallurgy method, and the coating is prepared by the synchronous evaporation method of dual target material.
The coating exhibits good wear and corrosion resistance under high load and neutral salt spray corrosion conditions. The wear amount is less than 0.2g, the corrosion rate is less than 2.5g/m2, and the interface stress with the substrate is low. It is suitable for connecting metal tools on overhead transmission lines, which can effectively ensure the safe and stable operation of the line and reduce operation and maintenance costs.
Smart Images

Figure CN112063970B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a wear-resistant and corrosion-resistant coating, in particular to a transitional wear-resistant and corrosion-resistant coating for electric power connection hardware and a preparation method thereof. Background Art
[0002] Power fittings are metal components that connect and combine various devices in the power system and are used for mechanical transmission, electrical load and device protection. As a type of fittings widely used in overhead transmission lines, connecting fittings should have high mechanical strength, good wear resistance and corrosion resistance to avoid large-scale power outages and other power grid safety accidents caused by fitting damage.
[0003] Most of the connecting fittings in the existing overhead transmission lines are made of carbon structural steel or alloy structural steel with a tensile strength greater than 375MPa, and some are made of malleable cast iron or ductile iron. When the line passes through a strong wind and sand area, the wind causes intense friction between the fittings, and the sand particles continuously impact the surface of the fittings, causing severe wear of the fittings and a decrease in the effective bearing area, thus causing line disconnection and power outage accidents.
[0004] In addition, hot-dip galvanizing is mainly used for corrosion protection of connecting fittings. However, since a large amount of hexavalent chromium ions in the plating solution can cause water and soil pollution, hot-dip galvanizing is now a strictly controlled environmental technology, and its application scope is severely limited. And because the galvanized layer is soft and has poor bonding with the substrate, when wear occurs between the connecting fittings, the galvanized layer is easily damaged, causing the substrate of the fitting to be directly exposed to the corrosive environment, accelerating the failure and damage of the fittings. Therefore, it is necessary to provide a coating with excellent wear resistance and corrosion resistance and environmental protection. Summary of the invention
[0005] In order to make up for the deficiencies of the prior art, the present invention discloses a composite transitional wear-resistant and corrosion-resistant coating suitable for power connection fittings and having excellent wear resistance and corrosion resistance and a preparation method thereof. The present invention is implemented by adopting the following technical solutions:
[0006] A transitional wear-resistant and corrosion-resistant coating for an electric power connection fitting, the fitting comprising the following components in mass percentage: C≤0.15%, Si≤0.45%, 1.30%≤Mn≤1.60%, P≤0.025% and S≤0.020%, the coating comprising a bottom layer and a top layer, the bottom layer comprising the following components in mass percentage: 6.80%-7.50% nickel, 14.60%-15.40% chromium, 20.00% silicon carbide and the balance iron; the top layer comprising the following components in mass percentage: 5.30%-5.90% nickel, 11.10%-11.80% chromium, 40.00% silicon carbide and the balance iron.
[0007] Furthermore, the bottom layer includes: 7.0% to 7.50% nickel and 14.80% to 15.40% chromium.
[0008] Furthermore, the top layer includes: 5.50% to 5.90% nickel and 11.30% to 11.80% chromium.
[0009] Furthermore, the bottom layer is 24 μm to 28 μm thick; and the top layer is 44 μm to 48 μm thick.
[0010] Furthermore, the bottom layer has a thickness of 25 μm to 28 μm; and the top layer has a thickness of 45 μm to 48 μm.
[0011] The method for preparing any of the above transitional wear-resistant and corrosion-resistant coatings comprises:
[0012] 1) Preparing an iron-nickel-chromium alloy target;
[0013] 2) preparing silicon carbide target;
[0014] 3) Prepare the bottom layer and top layer coating.
[0015] Further, the step 1) comprises:
[0016] a) Smelt iron, nickel and chromium;
[0017] b) refining the molten material obtained in step a) at 2000° C. for 3 min to 5 min;
[0018] c) Casting with high purity graphite crucible;
[0019] d) cutting the ingot obtained in step c) into Cylindrical target.
[0020] Furthermore, the step a) includes placing an yttria crucible containing iron, nickel and chromium in an induction melting device at 0.06Pa to 0.1Pa, and then introducing argon gas to melt the iron, nickel and chromium at a pressure of 0.05MPa.
[0021] Furthermore, the step 2) comprises: pressing the ball-milled silicon carbide powder into The material rod is then sintered in a high-temperature furnace at 1600° C. for 15 hours to obtain the silicon carbide target.
[0022] Furthermore, the step 3) includes: using two electron guns and two water-cooled copper crucibles to synchronously evaporate the silicon carbide target and the iron-nickel-chromium alloy target, wherein the electron gun beam currents for preparing the iron-nickel-chromium alloy target and the silicon carbide target of the bottom layer are 0.68A~0.81A and 1.32A~1.56A respectively, the electron gun beam current for heating the hardware substrate is 0.09A~0.15A, the temperature is 800℃±20℃, the bracket rotation rate of the hardware substrate is 13r / min, and the coating deposition time is 30min~50min.
[0023] Furthermore, during the synchronous evaporation of the dual targets, the electron gun beam currents for preparing the iron-nickel-chromium alloy target and the silicon carbide target for the top layer are 0.44A-0.57A and 1.75A-1.98A respectively.
[0024] Compared with the closest prior art, the technical solution provided by the present invention has the following excellent effects:
[0025] (1) The composite transitional wear-resistant and corrosion-resistant coating proposed in the present invention has good wear resistance and corrosion resistance. Under the condition of a load of 100N and 60min, the wear amount of the coating is less than 0.2g. Under the condition of 48h neutral salt spray corrosion, the corrosion rate of the coating is less than 2.5g / m 2 The present invention realizes the gradual change of organizational structure and physical and chemical properties. The coating has a low interface stress with the substrate, which is particularly suitable for the design and manufacture of connecting fittings for overhead power transmission lines. It can effectively ensure the safe and stable operation of the line and reduce the operation and maintenance costs of the line.
[0026] (2) The preparation method of the composite transitional wear-resistant and corrosion-resistant coating proposed in the present invention is fast and reliable. Iron, nickel and chromium are made into coating targets by induction melting, silicon carbide powder is made into coating targets by powder metallurgy, and the coating is prepared by dual-target synchronous evaporation method, which improves the efficiency of coating preparation and is suitable for actual production. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Schematic diagram of the composite transitional wear-resistant and corrosion-resistant coating and substrate structure provided by the present invention. DETAILED DESCRIPTION
[0028] In order to better understand the present invention, the content of the present invention is further described below in conjunction with the accompanying drawings of the specification. Unless otherwise specified, the percentages of the various components in the present invention are all mass percentages.
[0029] Example 1
[0030] The present invention adopts an induction melting method to make iron, nickel and chromium into coating targets, adopts a powder metallurgy method to make silicon carbide into coating targets, and adopts a dual-source synchronous evaporation method to prepare the coating. To avoid oxidation of alloy components, the coating preparation process is carried out in a vacuum chamber.
[0031] like Figure 1 As shown, the composite transitional wear-resistant and corrosion-resistant coating provided by the present invention is coated on the surface of the power connection hardware, and the composite coating includes: a bottom coating and a top coating. The preparation method provided in the embodiment is as follows:
[0032] 1) Preparation of substrate
[0033] The steel billet is processed into 20×15×3mm by wire cutting method. 3 A rectangular base is cut on each side of the front edge of the base. The round hole is convenient for hanging the substrate on the sample holder. Each surface of the substrate is polished with 300#, 500#, and 800# silicon carbide sandpaper to a surface roughness of R a <0.8.
[0034] 2) Preparation of Fe-Ni-Cr alloy target
[0035] The lump iron, nickel and chromium are weighed and mixed according to the mass percentage, and then put into an yttrium oxide crucible and placed in an induction melting device, and evacuated to 0.06Pa-0.1Pa. Argon gas is introduced to make the pressure in the inner cavity of the device reach 0.05MPa, and the power of the device is turned on. The raw materials are melted until they reach a clear state, and refined at 2000°C for 3min-5min. The power of the device is cut off, and a high-purity graphite crucible is used for casting to obtain an alloy ingot.
[0036] Fill the inner cavity of the equipment with air to break the vacuum state, take out the alloy ingot, and process it into Cylindrical target.
[0037] Repeat the above steps to obtain the iron-nickel-chromium alloy target material for the bottom layer and the iron-nickel-chromium alloy target material for the top layer in turn.
[0038] 3) Preparation of silicon carbide target
[0039] The silicon carbide powder is weighed and mixed according to the mass percentage and then placed in a ball mill. Alumina balls and anhydrous ethanol are used as grinding media. In order to ensure sufficient grinding, a mixed ball mill with grinding balls of diameters of 1mm, 5mm and 10mm in a quantity ratio of 10:5:1 is used. The mass ratio of the powder raw material, grinding balls and anhydrous ethanol is about 1:2:1.6. The ball mill is placed on a planetary ball mill and mixed for 12 hours. Then the slurry is quickly poured into a tray and dried in a drying oven at 90°C to obtain a uniform powder. The powder is placed in a stainless steel mold with an inner diameter of 68.5mm and pressed into a rod with a molding pressure of 90kN. The pressed rod is sintered in a high-temperature furnace at 1600°C for 15 hours to obtain. Repeat the above steps to obtain a bottom silicon carbide target and a top silicon carbide target.
[0040] 4) Preparation of base coating
[0041] The electron beam physical vapor deposition equipment with two electron guns and two water-cooled copper crucibles is used to realize the synchronous evaporation of the iron-nickel-chromium alloy target and the silicon carbide target.
[0042] The iron-nickel-chromium alloy target and the silicon carbide target were placed in water-cooled copper crucibles respectively, and the deposition equipment was evacuated to 10 -3 Pa.
[0043] The electron gun beam current for evaporating the iron-nickel-chromium alloy target is 0.68A~0.81A, and the electron gun beam current for evaporating the silicon carbide target is 1.32A~1.56A. The electron gun beam current is fine-tuned to ensure that the two target materials are evaporated synchronously in equal proportion to the height.
[0044] The electron gun beam current for heating the substrate is 0.09A to 0.15A, the substrate temperature is controlled at 800°C ± 20°C, the substrate sample holder rotation rate is 13r / min, and the coating deposition time is 30min to 50min.
[0045] 5) Preparation of top coating
[0046] The electron beam physical vapor deposition equipment with two electron guns and two water-cooled copper crucibles is used to realize the synchronous evaporation of the iron-nickel-chromium alloy target and the silicon carbide target.
[0047] The iron-nickel-chromium alloy target and the silicon carbide target were placed in water-cooled copper crucibles respectively, and the deposition equipment was evacuated to 10 -3 Pa.
[0048] The electron gun beam current for evaporating the Fe-Ni-Cr alloy target is 0.44A~0.57A, and the electron gun beam current for evaporating the SiC target is 1.75A~1.98A. The electron gun beam current is fine-tuned to ensure that the two targets are evaporated synchronously in equal proportion to the height. The electron gun beam current for heating the substrate is 0.09A~0.15A, the substrate temperature is controlled at 800℃±20℃, and the substrate sample holder rotation rate is 13r / min. The coating deposition time is 60min~80min.
[0049] Example 2
[0050] The composite transitional wear-resistant and corrosion-resistant coating provided in this embodiment includes: a bottom layer with a thickness of 24 μm and a top layer with a thickness of 44 μm.
[0051] The bottom layer includes, by mass percentage, 6.80% nickel, 14.60% chromium, 20.00% silicon carbide and the balance iron.
[0052] The top layer includes, by mass percentage, 5.30% nickel, 11.10% chromium, 40.00% silicon carbide and the balance iron.
[0053] Example 3
[0054] The composite transitional wear-resistant and corrosion-resistant coating provided in this embodiment includes: a bottom layer with a thickness of 25 μm and a top layer with a thickness of 45 μm.
[0055] The bottom layer includes, by mass percentage, 7.00% nickel, 14.80% chromium, 20.00% silicon carbide and the balance iron.
[0056] The top layer includes, by mass percentage, 5.50% nickel, 11.30% chromium, 40.00% silicon carbide and the balance iron.
[0057] Example 4
[0058] The composite transitional wear-resistant and corrosion-resistant coating provided in this embodiment includes: a bottom layer with a thickness of 26 μm and a top layer with a thickness of 46 μm.
[0059] The bottom layer includes, by mass percentage, 7.20% nickel, 15.00% chromium, 20.00% silicon carbide and the balance iron.
[0060] The top layer includes, by mass percentage, 5.70% nickel, 11.50% chromium, 40.00% silicon carbide and the balance iron.
[0061] Example 5
[0062] The composite transitional wear-resistant and corrosion-resistant coating provided in this embodiment includes: a bottom layer with a thickness of 28 μm and a top layer with a thickness of 48 μm.
[0063] The bottom layer includes, by mass percentage, 7.50% nickel, 15.40% chromium, 20.00% silicon carbide and the balance iron.
[0064] The top layer includes, by mass percentage, 5.90% nickel, 11.80% chromium, 40.00% silicon carbide and the balance iron.
[0065] The performance parameters of Examples 2-5 are shown in Table 1. As can be seen from Table 1, according to the requirements of GB / T12444-2006, under the conditions of a load of 100N and 60min, the wear loss of the composite transitional wear-resistant and corrosion-resistant coating provided by the present invention is less than 0.2g. According to the requirements of GB / T 10125-2012, under the conditions of 48h neutral salt spray corrosion, the corrosion rate of the composite transitional wear-resistant and corrosion-resistant coating provided by the present invention is less than 2.5g / m 2 .
[0066] Table 1. Performance parameters of the composite transitional wear-resistant coating obtained in the embodiment
[0067] Example Wear amount / g <![CDATA[Corrosion rate / g / m 2 > Vickers hardness / HV Elastic modulus / GPa 2 0.19 2.47 687 292.9 3 0.17 2.21 702 309.7 4 0.16 2.15 714 315.3 5 0.13 2.06 739 328.6 Hardware material 0.63 44.39 138 192.4
[0068] The above are merely embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention are included in the scope of the claims of the present invention to be approved.
Claims
1. A transitional wear-resistant and corrosion-resistant coating for a power connection fitting, the fitting comprising the following components by mass percentage: C≤0.15%, Si≤0.45%, 1.30%≤Mn≤1.60%, P≤0.025% and S≤0.020%, characterized in that: The coating comprises a bottom layer and a top layer, wherein the bottom layer comprises the following components by mass percentage: 6.80% to 7.50% nickel, 14.60% to 15.40% chromium, 20.00% silicon carbide and the balance iron; the top layer comprises the following components by mass percentage: 5.30% to 5.90% nickel, 11.10% to 11.80% chromium, 40.00% silicon carbide and the balance iron The bottom layer is 24 μm to 28 μm thick; The top layer is 44 μm to 48 μm thick; The preparation method of the transitional wear-resistant and corrosion-resistant coating comprises: 1) Preparation of iron-nickel-chromium alloy target; 2) Preparation of silicon carbide target; 3) Prepare bottom and top coatings; The step 3) comprises: using two electron guns and two water-cooled copper crucibles to synchronously evaporate the silicon carbide target and the iron-nickel-chromium alloy target, wherein the electron gun beam currents for preparing the iron-nickel-chromium alloy target and the silicon carbide target of the bottom layer are 0.68A-0.81A and 1.32A-1.56A respectively, the electron gun beam current for heating the hardware substrate is 0.09A-0.15A, the temperature is 800°C±20°C, the support rotation rate of the hardware substrate is 13r / min, and the coating deposition time is 30min-50min; During the synchronous evaporation of the dual targets, the electron gun beam currents for preparing the iron-nickel-chromium alloy target and the silicon carbide target for the top layer are 0.44A-0.57A and 1.75A-1.98A respectively.
2. The transitional wear-resistant and corrosion-resistant coating according to claim 1, characterized in that: The bottom layer includes: nickel 7.0%-7.50% and chromium 14.80%-15.40%.
3. The transitional wear-resistant and corrosion-resistant coating according to claim 1, characterized in that: The top layer includes: nickel 5.50%-5.90%, chromium 11.30%-11.80%.
4. The transitional wear-resistant and corrosion-resistant coating according to claim 1, characterized in that: The bottom layer is 25 μm to 28 μm thick; the top layer is 45 μm to 48 μm thick.
5. The transitional wear-resistant and corrosion-resistant coating according to claim 1, characterized in that: The step 1) comprises: a) Smelt away iron, nickel and chromium; b) refining the molten material obtained in step a) at 2000° C. for 3 min to 5 min; c) Casting with high purity graphite crucible; d) The ingot obtained in step c) is wire-cut into a cylindrical target material with a diameter of 68.5 mm.
6. The transitional wear-resistant and corrosion-resistant coating according to claim 5, characterized in that: The step a) comprises placing an yttria crucible containing iron, nickel and chromium in an induction melting device at 0.06Pa-0.1Pa, introducing argon gas, and melting the iron, nickel and chromium at a pressure of 0.05MPa.
7. The transitional wear-resistant and corrosion-resistant coating according to claim 1, characterized in that: The step 2) comprises: pressing the ball-milled silicon carbide powder into a material rod of φ68.5 mm, and then sintering it in a high-temperature furnace at 1600° C. for 15 hours to obtain the silicon carbide target material.
Citation Information
Patent Citations
Thermal spraying method used for improving wear resistance of overhung fittings of power transmission lines
CN106939400A
Power transmission line hardware corrosion resistance composite coating process
CN107034426A